PERAN RUPBASAN (RUMAH PENYIMPANAN BENDA SITAAN NEGARA) DALAM PENEGAKAN HUKUM - Sigit Setyadi (Universitas Janabadra, 2016)
AbstractConfiscated objects are obtained due to criminal cases, has given rise to a complicated problem because in addition to its importance as evidence in court proceedings, as well as its value is very precious, good value for the case, as well as the nominal value, especially in a big case like corruption. For that research in Yogyakarta, especially in Bantul, the problem